Developpemnt Du Capital Humain, Croissance Economique Et Bien-Etre En Côte d’Ivoire - Koné, Seydou (European Scientific Journal, ESJ, 2016)
This paper assesses human capital development policies and their impact on economic growth and householdsâ€™ well-being in CÃ´te d’Ivoire. A dynamic computable general equilibrium model was used to measure the impact of public spending on education and health policies as predicted by the government and then the effects of a larger increase of those spending on economic growth and household welfare in CÃ´te d’Ivoire. The simulations results show that public spending in education and health has positive impacts on education and health demands, on the improvement of laborâ€™s factor quality and on the productive capacities of poor and vulnerable households. The results also show that there is a positive correlation between public expenditures on education and health, economic growth and welfare in CÃ´te d’Ivoire.